Penerapan Metode Simple Additive Weighting (SAW) dalam Pemberian Reward Bagi Pegawai Honorer Menggunakan Pembobotan Rank Order Centroid - Tongam Panggabean; Mesran Mesran; Yessika Floriana Manalu (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Giving rewards to employees is one way to increase morale and improve performance for employees who excel. At the District Financial and Asset Management Agency. Deli Serdang in selecting the best employees, the workload cannot be used as the only reference for the awarding of these rewards. However, there are several criteria that are also considered in giving rewards. So we need a decision support system to help the selection of the best employees. In this study, the Simple Additive Weighting (SAW) method was chosen which was carried out by giving weighting to each criterion that was assessed per individual employee using the Rank Order Centroid (ROC) method. The criteria that are also assessed in this study are workload, attendance, discipline and work ethic of employees. Later, 3 employees who get the best score will be entitled to a reward.